The Effectiveness of Conceptual Map Teaching Method on Short and Long Term Learning in Nursing Students - Atefeh Ghanbari; Ezzat Paryad; Maryam Ehsani (Kerman University of Medical Sciences, 2011)
Background & Objective : Teaching basic principles of nursing cares requires applying innovative educational methods Conceptual map method as a new teaching strategy facilitates creative thinking teaching learning and evaluation processes This study aimed at comparing this method with traditional teaching methods in order to use the results for improving theoretical trainings and consequently the quality of nursing care services Methods : This semiexperimental study was performed in a pre & post test form Nursing students of one semester in Rasht Shaheed Beheshti Nursing & Midwifery School were taught 4 sessions of water and electrolytes by conceptual map method (experimental group) and the nursing students of the following semester were taught by the traditional method (control group) The two groups were compared by applying pre and post tests Data were analyzed through SPSS version 16 and by using Chisquare paired ttest and independent ttest Results : Teaching by conceptual map method could significantly (p